Pengaruh Branding, Packaging, Nilai Tambah Produk Hijau terhadap minat beli Produk Sepatu Aerostreet Kolaborasi dengan Le Minerale - Siti Masrokhah (ICON Publisher, 2024)
This study aims to analyze the impact of branding, packaging, and green product value addition on the purchase intention of Aerostreet shoes in collaboration with Le Minerale. With an increasing consumer awareness of environmental sustainability, it is essential to understand how these factors influence purchasing decisions. The objectives of this research are to determine the dominant variable affecting consumer purchase intention and to provide strategic insights for companies. A quantitative approach was employed, collecting data through an online survey of 100 respondents across Indonesia. The data were analyzed using multiple regression analysis with SPSS. The results indicate that branding, packaging, and green product value addition significantly affect consumer purchase intention, with branding emerging as the most influential factor. The study concludes that companies should focus on robust branding strategies, innovative packaging designs, and enhancing green product values to attract environmentally conscious consumers. However, the research is limited by its sample size and geographical scope. Future research should expand the sample size and explore additional variables to provide a more comprehensive understanding of consumer behavior in green marketing.